Implementation of Government Regulation Number 33 of 2012 concerning Exclusive Breastfeeding as a Form of Legal Protection for Babies Against the Promotion of Infant Formula Milk in Palembang City - Anastasya Megasstuti Gunadi; Endang Widyorini; Yovita Indrayati (SOEPRA, 2018)
Exclusive Breast Milk became the important programs prioritized by the Government with the Government Regulation Number 33 the Year 2012 about giving breast milk exclusively, in which the Government bans activities deemed to inhibit Exclusive breast feeding program, in particular, the promotion of baby formula. The purpose of this research is to know the implementation of government regulations Number 33 the Year 2012 of Exclusive breast feeding as a form of legal protection for infants against the promotion of baby formula in Palembang; restricting factor and factor endowments as well as the responsibility of the Government of the city of Palembang in the implementation of government regulations Number 33 Year 2012 of Exclusive breast feeding as a form of legal protection for infants against the promotion of baby formula in the city of Palembang.In this study, the author uses empirical juridical approach/sociological. This research is a descriptive analytic study. The analysis used in the study of qualitative analysis. Method of data collection used is through fieldwork using interviews and observations as well as through the study of librarianship by way of reading, collecting and studying as well as understand the source library.The results of this study are: (1) the implementation of PP No. 33 Year 2012 of Exclusive breast feeding has not been run with optimal in providing legal protection for infants against the promotion of baby formula in Palembang (2) supporting factors in the implementation of the Government Regulation No. 33 Year 2012 of Exclusive breast feeding as a form of legal protection for infants against the promotion of baby formula in Palembang is a city of Palembang has had local regulations Exclusive Breast Milk that is governing local regulations No. 2 the year 2014 of Exclusive breast feeding. While the factors restricting among other social and cultural factors in the community, working mothers, a lack of manpower counselors trained in hospitals (3) The responsibility of the Government of the city of Palembang Area Regulations run number 2 Year 2014 of Exclusive breast feeding as a follow-up of the Government Regulation (PP) number 33 Year 2012 of Exclusive breast feeding and run the application of sanctions a firm and tangible for those who violate and inhibit Exclusive breast feeding.